Hörer- und Sprechertypen in Bremen und Hamburg. Eine Untersuchung zu Sprachwissen, Sprachwahrnehmung und Sprachgebrauch - Hettler, Yvonne (Linguistik Online, 2017)
Regarding the perception of regional speech and the salience of language variants it is to as-sume, that they are being influenced by individual features of the specific speaker/listener. However, most recent studies dealing with the salience of language phenomena neglect factors like, for example, language awareness or the profession of speakers. This article focuses on the correlation between speech perception, speech production and individual characteristics of speakers like the metalinguistic knowledge they have. It presents selected results of a study dealing with the perception and production of regional speech in Bremen and Hamburg and discusses different types of speaker/listener profiles.